POLA AKTIVITAS PEKERJA SEKS KOMERSIL DALAM MENGGAET PELANGGAN DI JEMBATAN KENANGAN DESA SUKA JAYA KECAMATAN KEDURANG ILIR BENGKULU SELATAN - NIRWANSYAH, DIAN - (Pendidikan Sosiologi, 2014)
Prostitution is a form of social disease should stop its spread in thecommunity. The fact remains there is prostitution in South Bengkulu existing one onthe bridge of memories, which originated from the cafes in the bridge verges laterdeveloped into prostitution bridge memories. Prostitution was born because of age,body (body) that do not support anymore, because they have to compete with muchyounger prostitute her age, while sex workers on the bridge of memories have Â± 30years of age or older. This research used a qualitative approach with descriptive typeis a portrait of prostitution incident bridge memories. By taking 12 informants,including one pimp / pimp, prostitute 6, and 5 customers. The reason for using thisresearch to provide flexibility and opportunity for researchers to be able to digdeeper, because the case that the lift is very sensitive. Data collection was conductedby means of participant observation, in-depth interviews, and documentation.Findings indicate that the pattern of activity in the commercial sex workers to pick upmemories dijembatan customers Suka Jaya Village Kedurang Ilir District of SouthBengkulu, among others: (a) preparation of starting the activity, (b) the time patternof prostitution bridge of memories, (c) strategy PSK in hook the customer, (d)payment system, (e) customer PSK memories bridge.